THE IMPLEMENTATION OF ISLAMIC EDUCATION IN SHAPING STUDENT CHARACTER AT SD PANCA BUDI MEDAN - Kamil; Akhlak Siddiq; Annisa Nurhasanah Sipayung; Asmita Zahara Lubis; Aulia Agustina; Ayu Indah Lestari (Alhamdulillah : Jurnal Agama Islam, 2026)
This study aims to analyze the implementation of islamic education in shaping students character at Panca Budi Elementary School, Medan. Character education based on Islamic values serves as an essential foundation for developing a generation that is not only intellectually competent but also spiritually, emotionally, and socially mature. This study employed a descriptive qualitative method with a case study approach. Data were collected through participant observation, in-depth interview with the principal, Islamic Education (PAI) teachers, classroom teachers, and students, as well as documentation of religious activities conducted at the school. The findings indicate that the implementation of Islamic education at Panca Budi Elementary School, Medan, is carried out through two main strategies: (1) the habituation of religious practies, including daily obligatory prayers, Dhuha prayer, congregational prayer, and Qur’an recitation (tadarus); and (2) consistent role modeling (uswah hasanah) demonstrated by teachers and school staff through exemplary Islamic behavior. Supporting factors include the strong commitment of the school management and foundation, active parental support, and adequate educational facilities and infrastructure. Meanwhile, the inhibiting factors include differences in students religious understanding at home and the influence pof the digital social environment outside the school. This study recommends strengthening collaboration among Islamic Education teachers, classroom teachers, and parents, as well as developing more measurable and sustainable methods for character evaluation.